The root zone: Soil physics and beyond - Lazarovitch, Naftali; Vanderborght, Jan; Jin, Yan; van Genuchten, Martinus Th. [UNESP] (Wiley, 2018)
This special section of Vadose Zone Journal (VZJ) contains 15 contributions focusing on the physical, biological, and chemical aspects of water and solute transport into and through the soil root zone, including root water and solute uptake. The papers stem from presentations at the 2016 Kirkham Conference, “The Root Zone: Soil Physics and Beyond,” which took place at the Sede Boqer campus of Ben-Gurion University of the Negev, Israel, during 10 to 14 April (https://www.soils.org/membership/divisions/soil-physics-andhydrology/ kirkham-conferences). Much consensus existed at the conference for a special VZJ section to reflect the importance of the soil root zone from many disciplinary perspectives (soil, environmental, agricultural, hydrologic, and atmospheric) and the complexity of the basic processes involved. The contributions deal with root zone processes at different scales and from different disciplinary viewpoints, while covering a broad range of topics from the very theoretical to important practical applications. Special emphasis is on novel measurement and modeling tools at various scales and the need for interdisciplinary research.